2021
DOI: 10.3389/fped.2021.645776
|View full text |Cite
|
Sign up to set email alerts
|

NEOGAMES: A Serious Computer Game That Improves Long-Term Knowledge Retention of Neonatal Resuscitation in Undergraduate Medical Students

Abstract: Background: Serious games are potential alternatives for supplementing traditional simulation-based education for neonatal resuscitation training. However, evidence regarding the benefits of using serious games to improve long-term knowledge retention of neonatal resuscitation in undergraduate medical students is lacking.Objective: We designed a serious computer game “NEOGAMES” to train undergraduate medical students in neonatal resuscitation in a cost-friendly and accessible way and to examine whether serious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 15 publications
(17 reference statements)
2
21
0
2
Order By: Relevance
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 92 published studies, VS was reported to be applied in the educational practice involving undergraduate medical students across 25 countries including the United States [26 studies ( 15 40 )], the United Kingdom [9 studies ( 41 49 )], Germany [7 studies ( 50 – 56 )], China [6 studies ( 10 , 57 61 )], Denmark [6 studies ( 62 – 67 )], France [4 studies ( 68 71 )], Japan [4 studies ( 72 75 )], Sweden [3 studies ( 76 78 )], Canada [3 studies ( 79 – 81 )], Netherlands [3 studies ( 82 84 )], Spain [3 studies ( 85 87 )], Australia [2 studies ( 88 , 89 )], Singapore [2 studies ( 90 , 91 )], Korea [2 studies ( 92 , 93 )], Finland [1 study ( 94 )], Italy [1 study ( 95 )], Ireland [1 study ( 96 )], Colombia [1 study ( 97 )], Pakistan [1 study ( 98 )], Thailand [1 study ( 99 )], Iran [1 study ( 100 )], Poland [1 study ( 101 )], Mexico [1 study ( 102 )], Norway [1 study ( 103 )], Saudi Arabia [1 study ( 104 )], and Switzerland [1 study ( 105 )]. The distribution of included studies among different continents was shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The second focus of VS-integrated learning contexts in undergraduate medical education was emergency and pediatric emergency medicine training, with 14 articles ( 10 , 16 – 18 , 29 , 30 , 34 , 39 , 51 , 55 , 68 , 79 , 93 , 101 ) published recently. Among them, eight studies ( 10 , 16 – 18 , 30 , 34 , 39 , 68 ) used VS-based teaching in pediatric emergencies. The VS simulators used in these studies were mainly based on virtual patient cases, and simulated the clinical critical events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than focusing on a single skill (e.g., endotracheal intubation) this computer game aims to teach the entire neonatal resuscitation algorithm. Unlike most published studies, which involved medical students (9,19,20) and expert neonatal professionals (17,21) as learners, we tested it on a group of resident students of varying experience, using a randomized control study design with the primary goal of testing short-and medium-/long-term knowledge retention [primary endpoint: compare knowledge retention of DGBL and classical training]. The analysis is done by comparing the DGBL group with an independent group undergoing classic training (e.g., 80 min theoretical teaching session provided by an expert neonatal trainer).…”
Section: Introductionmentioning
confidence: 96%
“…While it is questioned whether DGBL approach can fully replace classic teaching methodologies (9)(10)(11)(12), DGBL methods are known to be effective in checking what was learned and reinforcing motivation to enhance adult learning in medical education (13) and, more in general, in higher education (14). With particular regard to medical practice (14)(15)(16), and especially neonatal resuscitation (9,17,18), numerous existing studies demonstrate the effectiveness of DGBL/simulation methods in stimulating better learning. However, many of these studies lack a scoring baseline (pre-test), a subsequent follow up to evaluate knowledge retention, and/or a homogeneous and independent control group.…”
Section: Introductionmentioning
confidence: 99%